Comparative workplace employment relations: an analysis of practice in Britain and France (Basingstoke, 2016)
"This comprehensive study provides a perceptive portrait of workplace employment relations in Britain and France using comparable data from two large-scale surveys: the British Workplace Employment Relations Survey (WERS) and the French Enquete Relations Professionnelles et Negociations d'Entreprise (REPONSE). These extensive linked employer-employee surveys provide nationally-representative data on private sector employment relations in all but the smallest workplaces, and offer a unique opportunity to compare and contrast workplace employment relations under two very different employment regimes. An insightful read for all academics and students of employment, the findings also have implications for practitioners and policy-makers keen to identify and promote "best practice"."